Analisis Haiku dalam Film Tokyo Godfathers - Said, Mikal Muhammad; Anwar, Fithyani (JURNAL ILMU BUDAYA, 2025)
This article analyzes three haiku in the animated film Tokyo Godfathers (Satoshi Kon, 2003) to explain their meaning and function in the narrative structure. A qualitative–descriptive design employs two steps: (1) heuristic–hermeneutic reading of the haiku (identifying kigo/kireji; literal and connotative meanings); and (2) structural analysis mapping each haiku to the plot (setup–confrontation–resolution) by its point of appearance, causal links, and character change. Primary data are the film and haiku transcripts; secondary data cover haiku studies and film narratology. Findings shows that the first haiku marks the birth of the mission on Christmas Eve; the second offers maternal encouragement at mid-plot; the third closes accounts on New Year’s Eve. Together the haiku act as act markers, strengthen the home–return motif, and steer character transformation: Hana reconciles with her foster mother and returns Kiyoko, Gin faces his daughter, and Miyuki makes peace with her father.